2021
DOI: 10.1080/21645515.2021.1932216
|View full text |Cite
|
Sign up to set email alerts
|

Potential public health impact of the adjuvanted recombinant zoster vaccine among people aged 50 years and older in Beijing

Abstract: Herpes zoster (HZ) is a painful, unilateral rash which occurs upon reactivation of latent varicella zoster virus due to age-related immunity decline or immuno-suppression. In 2019, the recombinant zoster vaccine (RZV) was the first vaccine to be approved in China for HZ prevention. This study aimed to estimate the potential public health impact of RZV vaccination, compared with the status quo of no vaccination, in individuals ≥50 years of age (YOA) in Beijing, by adapting the published ZOster ecoNomic Analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
19
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 28 publications
5
19
2
Order By: Relevance
“…As HZ is a relatively common affliction 1 and recurrence is possible, 44 the current model predicted that only 8–9 people aged 50–59 years up to 13–18 people aged ≥80 years would need to be vaccinated with RZV to prevent one case of HZ in the various countries studied due to the long-term protection afforded by this vaccine. These results are well aligned with results from Canada, 52 Germany, 21–23 the UK, 20 China, 26 , 53 and Japan. 27 …”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…As HZ is a relatively common affliction 1 and recurrence is possible, 44 the current model predicted that only 8–9 people aged 50–59 years up to 13–18 people aged ≥80 years would need to be vaccinated with RZV to prevent one case of HZ in the various countries studied due to the long-term protection afforded by this vaccine. These results are well aligned with results from Canada, 52 Germany, 21–23 the UK, 20 China, 26 , 53 and Japan. 27 …”
Section: Discussionsupporting
confidence: 87%
“…Our prediction that the youngest cohort would avoid the greatest number of HZ cases with vaccination is aligned with three studies from Germany 21–23 and one from China. 26 Our predictions that the percentages of HZ and PHN cases avoided would increase with age (HZ: 17.8% to 23.7%; PHN: 16.2% to 23.7%) aligns with data from US, which predicted that 21% to 41% of HZ cases and 8% to 41% of PHN cases would be prevented among people vaccinated at age 50 to 70 years, respectively. 17 …”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…The authors suggested that >14,000 hospitalizations and >1,000,000 outpatient visits could be avoided. Patients between 50 and 59 years had the greatest overall reduction in HZ cases, complications, and related healthcare resource use [101].…”
Section: Vaccinationmentioning
confidence: 99%